The Political Economy of Argentina, 1946–83 - Di Tella, Guido. author. aut Link
XVI, 349 p.
Keywords: Twelve international economists analyze every government since Peron's first presidency, including the latest military administrations. The years 1958-74 are examined in a new light and the postscript refers to President Alfonsin's changing economic strategy in his first years of government.